Dinitrogen Binding at a Trititanium Chloride Complex and Its Conversion to Ammonia under Ambient Conditions. Issue 34 (11th July 2022) - del Horno, Estefanía; Jover, Jesús; Mena, Miguel; Pérez‐Redondo, Adrián; Yélamos, Carlos
Abstract: Reaction of [TiCp*Cl3 ] (Cp*=η 5 ‐C5 Me5 ) with one equivalent of magnesium in tetrahydrofuran at room temperature affords the paramagnetic trinuclear complex [TiCp*(μ‐Cl)3 (μ3 ‐Cl)], which reacts with dinitrogen under ambient conditions to give the diamagnetic derivative [TiCp*(μ‐Cl)3 (μ3 ‐η 1 : η 2 : η 2 ‐N2 )] and the titanium(III) dimer [TiCp*Cl(μ‐Cl)2 ]. The structure of the trinuclear mixed‐valence complexes has been studied by experimental and theoretical methods and the latter compound represents the first well‐defined example of the μ3 ‐η 1 : η 2 : η 2 coordination mode of the dinitrogen molecule. The reaction of [TiCp*(μ‐Cl)3 (μ3 ‐η 1 : η 2 : η 2 ‐N2 )] with excess HCl in tetrahydrofuran results in clean NH4 Cl formation with regeneration of the starting material [TiCp*Cl3 ]. Therefore, a cyclic ammonia synthesis under ambient conditions can be envisioned by alternating N2 /HCl atmospheres in a [TiCp*Cl3 ]/Mg(excess) reaction mixture in tetrahydrofuran. Abstract : The reduction of [TiCp*Cl3 ] with magnesium leads to a mixed‐valence titanium species capable of reacting with dinitrogen to form a stable trinuclear complex with a η 1 : η 2 : η 2 ‐N2 ligand. This dinitrogen complex further reacts cleanly with HCl to produce NH4 Cl with regeneration of the titanium precursor. Thus, a cyclic ammonia synthesis under ambient conditions can be envisaged.